Impaired Vasodilatory Responses of Omental Arteries to CGRP Family Peptides in Pregnancies Complicated by Fetal Growth Restriction - Chauhan, Madhu (J Clin Endocrinol Metab, 2016)
RATIONALE: Calcitonin gene-related peptide (CGRP), adrenomedullin (ADM), and adrenomedullin2 (ADM2)/intermedin are potent vasorelaxant peptides considered to play a role in the adaptive mechanisms in rat pregnancy through increased vasodilation in mesenteric and uterine artery. OBJECTIVE: This study was designed to demonstrate the response of omental arteries (OA) to vasoactive peptides CGRP, ADM, and ADM2 in pregnancy complications such as fetal growth restriction (FGR), and assess the changes in the expression of their receptor components in segments of OA from FGR pregnancy compared to the control. FINDINGS: The findings for this study are: 1) relaxation responses of OA were higher for bradykinin (78.55 ± 3.91 vs 52.67 ± 2.19; P < .05) in pregnancy with FGR compared to the normal, 2) relaxation response of OA segments to CGRP was similar with no change in the expression of G-protein couple receptor-calcitonin receptor-like receptor complex in normal healthy pregnancy and pregnancy complicated by FGR, 3) maximal relaxation response of OA were significantly (P < .05) lower for both ADM (18.2 ± 6.7 vs 38 ± 2.5) and ADM2 (26.9 ± 6.7 vs 48 ± 2.6) along with decreases in their respective ligand-receptor complex in FGR compared to the normal pregnancies, 4) expression of calcitonin receptor-like receptor mRNA was higher but its immunoreactivity was lower in OA from FGR pregnancy compared to the normal, and 5) mRNA and protein levels of RAMP1, RAMP2, and RAMP3 were lower in OA isolated from FGR pregnancies compared to the normal. CONCLUSION: The current study demonstrates that FGR is associated with an increase in the sensitivity of OA to bradykinin and decreased sensitivity for ADM and ADM2 ligand-receptor system with no change in the response for CGRP compared to the normal healthy pregnancy, and suggests a potential role for ADM and ADM2 in the pathophysiology of maternal vasculature in FGR pregnancy.